Sugar intake is associated with progression from islet autoimmunity to type 1 diabetes: the Diabetes Autoimmunity Study in the Young - Lamb, Molly M. (Diabetologia, 2015)
AIMS/HYPOTHESIS: Dietary sugar intake may increase insulin production, stress the beta cells and increase the risk for islet autoimmunity (IA) and subsequent type 1 diabetes. METHODS: Since 1993, the Diabetes Autoimmunity Study in the Young (DAISY) has followed children at increased genetic risk for type 1 diabetes for the development of IA (autoantibodies to insulin, GAD or protein tyrosine phosphatase-like protein [IA2] twice or more in succession) and progression to type 1 diabetes. Information on intake of fructose, sucrose, total sugars, sugar-sweetened beverages, beverages with non-nutritive sweetener and juice was collected prospectively throughout childhood via food frequency questionnaires (FFQs). We examined diet records for 1,893 children (mean age at last follow-up 10.2 years); 142 developed IA and 42 progressed to type 1 diabetes. HLA genotype was dichotomised as high risk (HLA-DR3/4,DQB1*0302) or not. All Cox regression models were adjusted for total energy, FFQ type, type 1 diabetes family history, HLA genotype and ethnicity. RESULTS: In children with IA, progression to type 1 diabetes was significantly associated with intake of total sugars (HR 1.75, 95% CI 1.07–2.85). Progression to type 1 diabetes was also associated with increased intake of sugar-sweetened beverages in those with the high-risk HLA genotype (HR 1.84, 95% CI 1.25–2.71), but not in children without it (interaction p value = 0.02). No sugar variables were associated with IA risk. CONCLUSIONS/INTERPRETATION: Sugar intake may exacerbate the later stage of type 1 diabetes development; sugar-sweetened beverages may be especially detrimental to children with the highest genetic risk of developing type 1 diabetes.